The Reflecting the Value of Legal Certainty in the Conviction System for the Criminal Act of Bribery - Hadi Prayitno, Ahmad (Law Development Journal, 2023)
The perpetrator of assisting bribery in a succession of criminal acts holds a significant role, which has legal implications that necessitate thorough and conclusive investigations into those who assist in bribery. In looking at the position of perpetrators of assisting bribery, the ambiguity of Article 15 of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption has had a major impact on the rechtsvacuum in the criminal conviction system in bribery criminal policies. Through a normative method, this article's investigation reveals that convictions in bribery cases extend beyond only the active and passive perpetrators. Evidently, individuals who abet on bribery cannot be disregarded. Moreover, the ambiguity of the rules regarding assisting bribery, Article 15 of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, has created a rechtsvacuum in terms of convicting those involved in bribery cases. This scenario unequivocally leads to ambiguity in enforcing criminal penalties for bribery assistance perpetrators.